back to the math tutorial index back to the math tutorial index

Product Rule for Derivatives

In Calculus and its applications we often encounter functions that are expressed as the product of two other functions, like the following examples:

  • $h(x) = x e^x = (x)(e^x),$

  • $h(x) = x^2 \sin x = (x^2)(\sin x),$

  • $h(x) = e^{-x^2} \cos 2x = (e^{-x^2})(\cos 2x).$
In each of these examples, the values of the function $h$ can be written in the form $$ h(x) = f(x) g(x) $$ for functions $f(x)$ and $g(x)$. If we know the derivative of $f(x)$ and $g(x)$, the Product Rule provides a formula for the derivative of $h(x) = f(x) g(x)$:

$h'(x) = \left[f(x)g(x)\right]' = f'(x) g(x) + f(x) g'(x).$


We illustrate this rule with the following examples.

  • If $h(x) = x e^x $ then \begin{eqnarray*} h'(x) &=& (x)' e^x + x (e^x)'\\ &=& e^x + xe^x. \end{eqnarray*}

  • If $h(x) = x^2 \sin x $ then \begin{eqnarray*} h'(x) &=& (x^2)' \sin x + (x^2)(\sin x)'\\ &=& 2x \sin x + x^2 \cos x. \end{eqnarray*}

  • If $h(x) = e^{-x^2} \cos 2x $ then \begin{eqnarray*} h'(x) &=& (e^{-x^2})' \cos 2x + e^{-x^2} (\cos 2x)' \\ &=& -2xe^{-x^2} \cos 2x -2e^{-x^2} \sin 2x. \end{eqnarray*}

Key Concepts

Product Rule

Let $f(x)$ and $g(x)$ be differentiable at $x$. Then $h(x) = f(x)g(x)$ is differentiable at $x$ and $h'(x) = f'(x)g(x) + f(x)g'(x)$.